Analisis Praktik International Human Resource Management dan Global Talent Management dalam Mendorong Kinerja Organisasi Berkelanjutan pada Perusahaan Multinasional - Muhammad Sahrul Ramadhan; Bintang Restu Nanda; Ari Anggarani Winadi Prasetyoning Tyas (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This context necessitates a critical reassessment of International Human Resource Management (IHRM) and Global Talent Management (GTM) practices to sustain employee engagement and long-term organizational performance—especially in emerging markets like Indonesia, where glocal (global-local) tensions shape HR dynamics. This study aims to analyze how IHRM and GTM strategies contribute to enhancing employee engagement and sustainable organizational performance in MNCs. Using a qualitative approach with a descriptive-analytical design, this research employs library research. The population comprises peer-reviewed academic literature; the sample consists of 10 purposively selected journal articles (2018–2025). Data were collected via documentation and systematic keyword searches (e.g., “Global Talent Management”, “Employee Engagement”) across academic databases (Emerald, Springer, ProQuest, MDPI). Sources include scholarly journals, research reports, and case studies of MNCs in Indonesia. Data analysis applied content and thematic analysis through three stages: data reduction, thematic categorization, and conclusion drawing. The findings reveal three core pillars: (1) digital transformation as a strategic enabler for talent management, (2) glocal strategy integration balancing global standards and local adaptation, and (3) language competence (particularly English) as essential career capital. Furthermore, human-centric HR practices and inclusive employee voice mechanisms significantly strengthen emotional, cognitive, and behavioral engagement. The study implies that MNCs should adopt adaptive IHRM frameworks that harmonize global cohesion, cultural sensitivity, and ethical digital integration key for talent retention, organizational resilience, and sustainable competitiveness in volatile global markets.